2016
DOI: 10.1037/xlm0000171
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-induced versus context-induced forgetting: Does retrieval-induced forgetting depend on context shifts?

Abstract: Retrieval-induced forgetting (RIF) is the observation that retrieval of target information causes forgetting of related non-target information. A number of accounts of this phenomenon have been proposed, including a context-shift based account (Jonker, Seli, & Macleod, 2013). This account proposes that RIF occurs due to the context shift from study to retrieval practice, provided there is little context shift between retrieval practice and test phases. We tested both claims put forth by this context account. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Given equal initial states of activation, the disadvantageous activation of the retrieval-practice context only for Rp-items, but not for Nrp-items, still should have impaired the recall of Rp-items. The present challenge of the context-change account of RIF is in line with very recent work indicating that a change in mental context is neither necessary nor sufficient for RIF to occur (Buchli, Storm, & Bjork, 2015;Soares, Polack, & Miller, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…Given equal initial states of activation, the disadvantageous activation of the retrieval-practice context only for Rp-items, but not for Nrp-items, still should have impaired the recall of Rp-items. The present challenge of the context-change account of RIF is in line with very recent work indicating that a change in mental context is neither necessary nor sufficient for RIF to occur (Buchli, Storm, & Bjork, 2015;Soares, Polack, & Miller, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, a more recent, alternative (noninhibitory) theory based on changes in context ( Jonker, Seli, & MacLeod, 2013 ) argues that the retrieval practice paradigm produces RIF because the context at test more closely matches the context at retrieval practice than the context at original study. Jonker et al found that RIF could be eliminated following manipulations at test that helped reinstate the original study context (a claim that has itself already attracted some counterclaims, see Chan, Erdman, & Davis, 2015 ; Soares, Polack, & Miller, 2016 ).…”
mentioning
confidence: 99%
“…First, the trial markers (TM) borders were made unique across conditions (see Figure S1). We did this to avoid a potential TM-contextual carryover effect that might have enhanced similarlity between conditions, given that trial context can be a crucial factor for judgments and behaviour in humans (e.g., Msetfi, Wade, & Murphy, 2013;Soares, Polack, & Miller, 2016), as well as for expressing learning by nonhumans (Jozefowiez, Witnauer, & Miller, 2012;Murphy, Baker, & Fouquet, 2001;Urcelay, Witnauer, & Miller, 2012; for a review see also Urcelay & Miller, 2014). Second, we added a discrete context stimulus that was unique for each condition to enhance the distinctiveness of the contexts in each condition (Murphy & Baker, 2004;Waugh & Norman, 1965).…”
Section: Methodsmentioning
confidence: 99%